DiscoverFriends: secure social network communication in mobile ad hoc networks. Issue 11 (10th August 2016) - Joy, Joshua; Chung, Eric; Yuan, Zengwen; Li, Jiayao; Zou, Leqi; Gerla, Mario
Abstract: This paper presents a secure communication application called DiscoverFriends. Its purpose is to securely communicate to a group of online friends while bypassing their respective social networking servers under a mobile ad hoc network environment. DiscoverFriends leverages Bloom filters and a hybrid encryption technique with a self‐organized public‐key management scheme to securely identify friends and provide authentication. Additionally, DiscoverFriends enables anonymous location check‐ins by utilizing a new cryptographic primitive called function secret sharing. Finally, to the best of our knowledge, DiscoverFriends implements and evaluates the first Android multi‐hop WiFi direct protocol using IPv6. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Online social networks (OSNs) with location‐based services have seen a notable increase in usage on mobile devices. However, location‐based services have privacy concerns ‐ the ability for an OSN to track individuals' activities. We present DiscoverFriends, the first Wi‐Fi multi‐hop solution that bypasses OSN servers, enabling users to communicate with their OSN friends without having to go through OSN servers.